Critical analysis of archaeological research trends in Uganda: 1920-2018 - Kinyera Okeny, Charles; Kyazike, Elizabeth; Gumoshabe, Gilbert (African Journal of History and Culture, 2020)
Much as the first collections of stone tools in East Africa were made by geologist J.W. Gregory, beginning in 1893, E.J. Wayland’s joined the government service in Uganda in 1919 to set East African Archaeology on the course that it was to follow for the next 40 years or more. However, over 90 years from its inception, a larger percentage of archaeological research in Uganda seems regionally imbalanced, dominated by foreign researchers and periodically generalized. In order to understand these anomalies, this study undertook a critical literature review of archaeological research data from 1920 to 2018. The main objectives were to; document the regional distribution of archaeological research in Uganda; analyze the interplay between local and foreign researchers, and examine the period of archaeological research, that is Stone Age or Iron Age. Results show that, there is a wide gap in regional distribution of archaeological research in Uganda, dominated by foreign researchers with a focus on Iron Age period. The study concludes that, the limited research interest in other parts of Uganda is not because of lack of archaeology but a long set ideology of foreign researchers to dominate local research space. This calls for active involvement of local researchers in archaeological research, in order to neutralise the long set colonial research ideology and take charge of archaeological research directions. This will aid in narrowing the regional research gaps as well as presenting the true picture of Uganda’s past.
Keywords: Archaeology; archaeological potential; stone age